Mouse Model for Platelet Aggregation using Flow Cytometry. (9th November 2022) - Gordy, Dominique; Stone, Elizabeth
Abstract: Platelets play crucial roles in hemostasis, bleeding, and thrombosis. Within the United States, an estimated 7, 000 platelet units are transfused daily. The gold standard to measure platelet survival in humans is to determine post-transfusion recovery after an autologous transfusion of radiolabeled platelet units, however, the ability to detect platelets circulating after transfusion does not provide information on how well these platelets function in hemostasis. Clinically, platelet unit function is routinely measured using aggregometry, which requires large volumes of platelet concentrates and normal platelet counts. While the clinical demand for platelets continues to increase with advances in medical care, there remains a lack of in vitro measures to properly assess platelet function in animal models. Here we outline an in vitro method for characterizing platelet function using flow cytometry to assess platelet activation and aggregation simultaneously in a mouse model. Using two commercially available transgenic mouse lines, one with platelets expressing red fluorescent protein (RFP) and the other with platelets expressing green fluorescent protein (GFP), whole blood is collected from each transgenic mouse line by aseptic cardiac puncture, and leukocyte-reduced platelet rich plasma (LRPRP) is isolated after two consecutive centrifuge spins and leukocyte reduction. RFP- and GFP-labeled platelets can be visually separated by flow cytometry. Platelets are activated after incubation with 4 mM GPRP peptide followed by exposure to 0.5U/mL high activity bovine thrombin for 2 minutes. Platelets are then stained with anti-CD41a, labelling all platelets, and anti-CD62P, labelling activated platelets; these platelet populations can be analyzed by flow cytometry. When RFP- and GFP-LRPRP are combined prior to activation with thrombin, RFP- and GFP-labeled platelet aggregation can be measured as the number of cells doubly expressing RFP and GFP by flow cytometry. Thrombin stimulation activated 93.31% of the total number of RFP- and GFP-platelets. Of the activated, CD62P-positive platelets, 11.03% expressed both RFP and GFP, indicating that these platelets were aggregated. Of the inactivated, CD62P-negative platelets, 0.81% expressed both RFP and GFP. These results suggest that thrombin exposure activates platelets and causes platelet aggregation, while <1% of inactivated platelets aggregate. Additionally, platelet aggregation is easily measured by flow without differentially labeling the two separate platelet populations. These data indicate that our model is a viable measure of platelet function in vitro . Our model of platelet activation and aggregation provides a baseline measure of in vitro platelet function in RFP and GFP mice. This in vitro method of assessing platelet function can be applied to various experimental populations and used to quantify the effects of experimental conditions on platelet function in mice. Using this model of platelet function, factors influencing platelet storage can be characterized and ultimately used to improve platelet transfusion therapies.